Otroci, rojeni po oploditvi z biomedicinsko pomočjo - Kornhauser-Cerar, Lilijana (Medicinski razgledi, 2005)
For as long as assisted reproductive technologies (ARTs) have been used, therehas been an ongoing concern as to whether they might have an impact on pregnancy course and especially on the outcome of children. Currently, there is convincing evidence that ART treatment may increase the risk of a few adverse outcomes. These include the increased rate of multiple gestation pregnancies due to multiple embryo transfers or to embryo splitting that carries a higher risk of preterm delivery and therefore, of increased morbidity and mortality in newborns. Further, even singletons conceived with all types of ART appear to be at a higher risk of preterm birth and low birth weight. An increase in abnormalities among pregnancies concieved using intracytoplasmic sperm injection (ICSI) has been suggested. However, there areuncertainities whether this is a direct treatment effect or is related to parental infertility factors, or a combination of both. For some other outcomes, such as increased risk for genetic imprinting disorders, specific neonatal morbidities, birth defects, retinoblastoma, and developmental disabilities, data are inconsistent as there were no purposeful study of sufficient size and scope performed. To date, there is no or very little evidence of ART-effects on the childhood cancers, chronic illnesses, learning or behavioural disorders, and reproductive effects. Further large, well-designed, long-term studies are needed to separate treatment effects frominfertility effects and to identify areas where ART treatments could be improved in ways that would minimize the risks for some adverse outcomes.
Keywords: Fertilization In Vitro; Nedonošenček; Nosečnost večplodna; Embryo Transfer; Novorojenček z nizko porodno težo; Pregnancy, Multiple; Oploditev in vitro; Infant, Premature; in vitro fertilization; Infant, Low Birth Weight; Zarodek, prenos; Infant Mortality; Anomalije; Abnormalities; Dojenček, umrljivost; Developmental Disabilities; Novorojenček; Infant, Newborn; Razvojne motnje; dojenčki; child; otroci; fertilization; oploditev; umetna oploditev; tveganje